(untitled) (World Bulletin of Physical Education and Sports Science, 2026)
This article examines the importance of judo as a sport in the physical and moral development of military cadets. Judo contributes not only to physical strength and endurance but also to discipline, responsibility, and psychological resilience. The study analyzes how judo training enhances combat readiness, teamwork, and leadership skills among cadets. The findings indicate that integrating judo into military education programs significantly improves both physical performance and character formation.